Quantum cascade laser spectroscopy: from trace gas detection to nonlinear optics - Pinto, T (2018)
Quantum cascade lasers (QCLs) are high power, narrow linewidth mid-IR lasers that are increasingly popular for trace gas sensing and nonlinear spectroscopy. This thesis demonstrates QCL based spectroscopic techniques for multi-species detection, nonlinear optics and trace gas detection, highlighting the versatility of these lasers. Firstly, a Fabry-Perot QCL (FP-QCL) operating at 5.3 μm was used to perform multi-mode absorption spectroscopy (MUMAS) for sensing of NO and H2O. The laser provides a spectral coverage of ca. 50 cm-1 with a time resolution down to the ms timescale. It also exhibits a frequency resolution of < 50 MHz, limited by the longitudinal mode linewidth. This was the first demonstration of MUMAS with QCLs. Secondly, the optical purity of a single mode distributed feedback (DFB) QCL operating at 5.3 μm was determined using Lamb-dip spectroscopy and by analysing the frequency noise power spectral density (PSD). Both methods revealed the linewidth of the device is ca. 500 kHz, which can be reproducibly broadened up to ˜∼8 MHz by applying broadband uncorrelated radio-frequency current perturbations. Thirdly, the DFB-QCL was used in combination with an external cavity (EC) QCL to study the evolution of velocity selected coherent signals in vibrationally excited NO. The coherent signatures showed lifetimes up to 378 ± 23 ns. Maximum population transfer to the v = 1 level was achieved after pumping for 10 ± 0.5 μs, and the decay time of post-pumping coherent transient signals was 5.7 ± 0.3 μs at a pressure of 3 mTorr. The collisional relaxation rate of the coherent systems was determined for various buffer gases, reaching (4.28 ± 0:13) ×104 s-1 mTorr-1 with CO2. Lastly, a DFB-QCL was used to demonstrate intracavity Faraday modulation spectroscopy (INFAMOS), a technique for the sensitive and selective detection of radicals, using NO as a test molecule. A model that predicts the INFAMOS lineshape was presented, and the sensitivity for the detection of NO was 0.21 ppbv Hz1/2, corresponding to a minimum detectable rotation angle of 0.16 nrad Hz1/2, at a total pressure of 412 Torr. Optical saturation effects were observed and included in the INFAMOS model.